Intrinsically disordered region of talin’s FERM domain functions as an initial PIP2 recognition site - Buhr, Jannik; Franz, Florian; Gräter, Frauke (Biophysical journal, 2023)
Focal adhesions (FAs) mediate the interaction of the cytoskeleton with the extracellular matrix in a highly dynamic fashion. Talin is a central regulator, adaptor protein, and mechano-sensor of FA complexes. For recruitment and firm attachment at FAs, talin’s N-terminal FERM domain binds to phosphatidylinositol 4,5-bisphosphate (PIP2)-enriched membranes. A newly published autoinhibitory structure of talin-1, where the known PIP2 interaction sites are covered up, lead us to hypothesize that a hitherto less examined loop insertion of the FERM domain acts as an additional and initial site of contact. We evaluated direct interactions of talin-1 with a PIP2 membrane by means of atomistic molecular dynamics simulations. We show that this unstructured, 33-residue-long loop strongly interacts with PIP2 and can facilitate further membrane contacts, including the canonical PIP2 interactions, by serving as a flexible membrane anchor. Under force as present at FAs, the extensible FERM loop ensures talin maintains membrane contacts when pulled away from the membrane by up to 7 nm. We identify key basic residues of the anchor mediating the highly dynamic talin-membrane interaction. Our results put forward an intrinsically disordered loop as a key and highly adaptable PIP2 recognition site of talin and potentially other PIP2-binding mechano-proteins.